Shaping The Future of Work Readiness of Internship Students : Role of Gen Z’s Resilience - Putri, Felita Alysia; Sulistiobudi, Rezki Ashriyana (Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the role of resilience on work readiness in MBKM (Merdeka Belajar Kampus Merdeka) internship students. Non-experimental correlational study design was used. A quantitative approach through regression and descriptive statistical analysis was used to analyze the collected data. Non-probability sampling, specifically the convenience sampling, was also used. Data collection was carried out through an online questionnaire using Google Forms. The respondents consisted of 140 students from a university in West Java who had participated in the MBKM internship program. The Resilience Quotient Test (RQ-Test) and Work Readiness Scale (WRS) were used to measure resilience and work readiness, respectively. The result of this study showed that resilience had a significant role on work readiness (r2 = 0.285; p = 0.000). This study is expected to present information and contribute theoretically towards resilience and its role towards work readiness in MBKM internship students. The result of this study can be used by students that participate in the internship program to evaluate themselves and to show them the importance of developing resilience for their work readiness in the future.